Common views from the commentators about accounting measurement / Sharifah Norhafiza Syed Ibrahim - Syed Ibrahim, Sharifah Norhafiza (2006)
Financial reporting aims at reporting relevant financial information, useful to users in evaluating present and past performance of an entity and making informed economic decisions in allocating economic resources. Despite significant development in regulating financial reporting in order to ensure that users are provided with sufficient level of financial information, many still find it difficult to interpret the financial information. The main area of concern is accounting measurement. Most accounting standards setters agree that accounting measurement is problematic. As the process of measurement is central to general purpose financial reporting, the attributes we choose to measure and the way we go about establishing the measurements, create images of financial performance, financial position, liquidity, capacity to adapt, cash generating potential and so on.